Mengintegrasikan Prinsip Syariah dalam Bisnis Digital: Pelatihan dan Pengembangan Mahasiswa Membangun Bisnis Digital yang Berkelanjutan - Nugroho, Adandy; Wulandari, Nova Tri; Wahid, Alfathur Amin; Sa'diyah, Nazhifatum Mutiara Salma; Fitriana, Fitriana (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The community service activity entitled "Integrating Sharia Principles in Digital Business: Training and Development for Students Building Sustainable Digital Business" was held to strengthen the ability of University of Sharia Accounting students to develop digital businesses that comply with sharia principles. Carried out in an interactive seminar format, this event focuses on introducing sustainable digital business concepts, digital marketing strategies, and the integration of sharia values in every aspect of business. The main speaker, Adandy Nugroho, S.Ds.., provided in-depth insights and relevant case studies to help students understand the role of technology in achieving business goals in accordance with Islamic values. The evaluation of the event showed active participation and high levels of satisfaction from participants, who felt better prepared to develop their business ideas. It is hoped that this activity can become a basis for students to run a business that is not only financially profitable but also has a positive social impact and is in accordance with sharia principles.